Developing Rural Tourism: A Potential Contribution To Achieving Sustainable Development Goals - Nisrina Nafi’atul Huda; Farid Ma'ruf; Hapsoro Agung Jamiko (Jurnal Ilmiah Teknik Industri, 2022)
Rural development is one of the primary keys to achieving sustainable development goals. Important changes in rural development strategies become inevitable and can be accommodated through rural tourism. Nonetheless, the models of rural tourism development, which depict the stages in developing and maintaining rural tourism, are still minimal. This research is conducted to fill the research gap by designing a conceptual model of rural tourism development. One-on-one interviews with four rural tourism development experts are done separately. The voice recording during the interviews is transcribed immediately after the interviews and proceeds with data processing using the qualitative coding method, which consists of open, axial, and selective coding. The qualitative coding method shows two main stages in rural tourism development: pre-development and development. The pre-development set consists of motivation and forum group discussion, while the development stage consists of planning, organization arrangement, HR development, product development, and marketing.